PERANCANGAN ADAPTASI CERITA RAKYAT “RANGKAYO HITAM” DALAM BENTUK KOMIK DIGITAL UNTUK MEMPERKENALKAN BUDAYA DAERAH PROVINSI JAMBI DI KALANGAN REMAJA USIA 15 – 25 TAHUN - Prasetya, Dimas; Sukmaraga, Ayyub Anshari; Nugroho, Didit Prasetyo (Ma Chung Press, Universitas Ma Chung, 2025)
Teenagers today are less interested in traditional culture. This is due to technological advancements that make the younger generation addicted to gadgets and outside culture. This threatens the existence of traditional culture. One of the threatened cultures is folklore. There are thousands of folktales throughout Indonesia that teach moral values and character education to children and adolescents. Therefore, it is important to reintroduce folklore to the younger generation by adapting it into media that is close to teenagers, namely digital media. One of the lesser-known folktales is a story from Jambi Province. One of them is entitled Rangkayo Hitam. The design of the folklore comic